New Data of the Genus Mediorhynchus (Acanthocephala, Archiacathocephala, Gigantorhynchidae) from Bulgarian Birds - Dimitrova, Z.M. (Вестник зоологии, 1999)
The investigations on a new faunistic material of avian acantho-cephalans collected during the period 1984—1995 from Bulgaria revealed the presence of 4 species of the genus Mediorhynchus.